ISSUES OF FORMATION OF METHODOLOGICAL COMPETENCE OF FUTURE TEACHERS OF NATURAL SCIENCE CYCLE IN THE PROCESS OF PROFESSIONAL TRAINING - Lavrentyeva, O.O. (Pedagogy of Higher and Secondary Education, 2010)
In work questions are considered, problems are analyzed and perspective directions of formation of methodological competence of the future teachers of a natural-science cycle in the course of vocational training are defined.